Prospective Results from the PA (Personality and Activity) Project: Evaluating the Influence of the Transtheoretical Model on Physical Activity while Considering Personality Trait Characteristics - Chelsea Joyner; Paul D. Loprinzi (Bilişsel Davranışçı Psikoterapi ve Araştırmalar Dergisi)
The Transtheoretical model (TTM) consists of a framework of five discrete stages adopted to study behavior change. Previous research demonstrates utility of the TTM in influencing physical activity. Personality trait characteristics have also been shown to influence physical activity. To date, limited research has evaluated whether the TTM influences physical activity across various personality traits. This studys purpose was to examine the prospective association of each of the TTM constructs on physical activity, with considerations by personality type, using the follow-up data from the PA (Personality and Activity) Project. Personality, physical activity, TTM constructs, and covariates were assessed via validated questionnaires. 126 participants with data at baseline and the 5-month follow-up constituted our analytic sample. The only TTM construct associated with follow-up moderate-to-vigorous (MVPA) was behavioral processes of change (β = 10.0; 95% CI: -0.34, 20.37; P=0.05). There were no significant interaction effects for any of the TTM constructs and personality types on follow-up MVPA. In conclusion, personality did not moderate the relationship between the TTM and future MVPA behavior. If confirmed by future research, these findings suggest that TTM-based physical activity interventions may not need to develop personality-matched TTM strategies. [JCBPR 2019; 8(1.000): 25-32]